The Micropropagation Potential and Regenerative Ability of Somatic Embryos of “Vitis Vinifera” ssp. “Sylvestris” (Gmel.) Hegi - POPESCU, Carmen Florentina (Studia Universitatis Babeș-Bolyai Biologia, 2016)
In this paper are presented the results obtained with Vitis vinifera ssp. sylvestris accessions subjected to the in vitro micropropagation. For clonal propagation were used meristematic tissues (apexes and axillary buds) aiming to establish an efficient protocol for long-term conservation or for virus-free plant recovery (if viruses were detected) applied to accessions belonging to seven different populations. The in vitro development showed particular aspects and significant differences among wild populations regarding their competence for differentiation, the moment of differentiation in inoculated explants, the aspect of proliferative structures and the rates of multiplication. The same accessions were tested also for their competence in plant regeneration by either organogenesis or embryogenesis starting from somatic tissues. Shoot regeneration and normal plants were obtained from petiole explants derived from in vitro grown shoots of the seven accessions. Callus induction was obtained with all genotypes on MS media supplemented with BAP and 2,4-D, or IBA, and the best direct adventitious shoot formation was obtained after transfer on medium supplemented with BAP and IAA. With anther culture, the genetic factors proved to be essential for callus induction and promoting the embryogenic process. Three, out of seven accessions, only male individuals, responded to anther culture by regeneration through embryogenesis on all used media with similar results, forming normal embryos, abnormal embryos and whole plants.